THE EFFECT OF ESA (ENGAGE STUDY ACTIVE) METHOD ON STUDENTS’ VOCABULARY MASTERY AT THE SEVENTH GRADE ON MTS Swasta DARUL AKHIROH BONAN DOLOK IN 2020/2021 ACADEMIC YEAR - yusra hartati (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract : The purpose of this research are to find out: 1) The application of ESA Method on students’ vocabulary mastery, 2) The students’ Vocabulary mastery before and after using ESA Method, 3) whether there is any significant effect of ESA Method on students’ vocabulary mastery at the seventh Grade of MTS SwastaDarulAkhirohBonandolok.This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research is all the VII Grade students’of MTS SwastaDarulAkhirohBonanDolokby using total sampling. In collecting the data, the researcher used observation sheet. Instrument of the research was observation and test was composition test. The result of the research are 1) application of ESA Methodwas 3.6, it was categorized “very good”. 2) The mean score of the students’ before using ESA Methodl was 26,07 it was categorized “bad”. Meanwhile after using ESA Method was 53,5. The result of analysis showed that ttest is bigger than ttable (ttest19.80>ttable 2.05). So, the hypothesis was accepted. It means that there is any significant effect of ESA method on students’ vocabulary mastery at the seventh grade of MTS SwastaDarulAkhirohBonanDolok.